N-Butylphthalide Improves Cognitive Function in Rats after Carbon Monoxide Poisoning - Bi, Ming-Jun; Sun, Xian-Ni; Zou, Yong; Ding, Xiao-Yu; Liu, Bin; Zhang, Yue-Heng; Guo, Da-Dong; Li, Qin (Frontiers in Pharmacology, 2017)
Cognitive impairment is the most common neurologic sequelae after carbon monoxide (CO) poisoning, and the previous investigations have demonstrated that N-Butylphthalide (NBP) could exert a broad spectrum of neuroprotective properties. The current study aimed to investigate the effect of NBP on cognitive dysfunction in rats after acute severe CO poisoning. Rats were randomly divided into a normal control group, a CO poisoning group and a CO+NBP group. The animal model of CO poisoning was established by exposure to CO in a chamber, and then all rats received hyperbaric oxygen therapy once daily, while rats in CO+NBP group were administered orally NBP (6mg/ 100g) by gavage twice a day additionally. The results indicated that CO poisoning could induce cognitive impairment. The ultrastructure of hippocampus was seriously damaged under TEM, and the expressions of calpain 1 and CaMK II proteins were significantly elevated after CO exposure according to the analysis of immunofluorescence staining and western blot. NBP treatment could evidently improve cognitive function, and maintain ultrastructure integrity of hippocampus. The expression levels of both calpain 1 and CaMK II proteins in CO+NBP group were considerably lower than that of CO poisoning group (P<0.05). Taken together, this study highlights the molecular mechanism of cognitive dysfunction in rats after CO exposure via the upregulation of both calpain 1 and CaMK II proteins. The administration of NBP could balance the expressions of calpain 1 and CaMK II proteins and improve cognitive function through maintaining ultrastructural integrity of hippocampus, and thus may play a neuroprotective role in brain tissue in rats with CO poisoning.